2019
DOI: 10.15171/jept.2019.14
|View full text |Cite
|
Sign up to set email alerts
|

The financial burden of imaging tests conducted in the emergency department of a teaching hospital: a brief report

Abstract: Objective: Each imaging technique has a special application and usage, and should be used in the right situation. Physicians choose the type of imaging technique by considering the type of tissue and the benefits and disadvantages of the imaging method as well as its financial burden on the patient. The aim of this study was to estimate the cost of imaging tests performed in the emergency department (ED) of an educational hospital and determine their financial burden on both the patients and the healthcare sys… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 10 publications
0
4
0
Order By: Relevance
“…Higher CT scan utilization leads to more diagnosis, and it also has more ionizing emissions than plain radiographs [ 43 ] and shows association with CNS tumours [ 44 ]. A recent report showed that the number of CT scans performed per each emergency room visit in an Iranian hospital in 2016 was about three times higher than world rates [ 45 ].…”
Section: Discussionmentioning
confidence: 99%
“…Higher CT scan utilization leads to more diagnosis, and it also has more ionizing emissions than plain radiographs [ 43 ] and shows association with CNS tumours [ 44 ]. A recent report showed that the number of CT scans performed per each emergency room visit in an Iranian hospital in 2016 was about three times higher than world rates [ 45 ].…”
Section: Discussionmentioning
confidence: 99%
“…However, regardless of this variation, imaging techniques are significant contributors to financial health costs; if used inadequately, this creates a financial burden for the health system and patients. For example, the total cost of performing different imaging services for patients coming through an emergency department in a teaching hospital stood at ≃$US 423 745 [3].…”
Section: Introductionmentioning
confidence: 99%
“…The raw mortality rate varies based on epidemiology, type of hospital, and social conditions; for example, the raw mortality rate in 2018 was 5.3% in Iran, 9.4% in France, 11.8% in Germany, 7.3% in India, and 10.5 in Italy [3,4]. Many of this death occurs in the emergency department of hospitals.…”
Section: Introductionmentioning
confidence: 99%
“…Many of this death occurs in the emergency department of hospitals. Factors like Intubation, low systolic blood pressure on presentation, increased age, and comorbidity can increase emergency department mortality rate, an epidemiologic study in Tehran, Iran, resulted in the mortality rate of patients who referred to the emergency department was 0.9% and the mortality rate in UMHAT -Pleven emergency department was 2.4/100000 [4][5][6].…”
Section: Introductionmentioning
confidence: 99%